Homo-oligomerization and Activation of AMP-activated Protein Kinase Are Mediated by the Kinase Domain αG-Helix - Scholz, Roland (American Society for Biochemistry and Molecular Biology, 2009)
AMP-activated protein kinase (AMPK) is a heterotrimeric complex playing a crucial role in maintaining cellular energy homeostasis. Recently, homodimerization of mammalian AMPK and yeast ortholog SNF1 was shown by us and others. In SNF1, it involved specific hydrophobic residues in the kinase domain αG-helix. Mutation of the corresponding AMPK α-subunit residues (Val-219 and Phe-223) to glutamate reduced the tendency of the kinase to form higher order homo-oligomers, as was determined by the following three independent techniques in vitro: (i) small angle x-ray scattering, (ii) surface plasmon resonance spectroscopy, and (iii) two-dimensional blue native/SDS-PAGE. Recombinant protein as well as AMPK in cell lysates of primary cells revealed distinct complexes of various sizes. In particular, the assembly of very high molecular mass complexes was dependent on both the αG-helix-mediated hydrophobic interactions and kinase activation. In vitro and when overexpressed in double knock-out (α1(−/−), α2(−/−)) mouse embryonic fibroblast cells, activation of mutant AMPK was impaired, indicating a critical role of the αG-helix residues for AMPK activation via its upstream kinases. Also inactivation by protein phosphatase 2Cα was affected in mutant AMPK. Importantly, activation of mutant AMPK by LKB1 was restored by exchanging the corresponding and conserved hydrophobic αG-helix residues of LKB1 (Ile-260 and Phe-264) to positively charged amino acids. These mutations functionally rescued LKB1-dependent activation of mutant AMPK in vitro and in cell culture. Our data suggest a physiological role for the hydrophobic αG-helix residues in homo-oligomerization of heterotrimers and cellular interactions, in particular with upstream kinases, indicating an additional level of AMPK regulation.